Implementation of the islamic quality management system MS1900 and its benefits: A case study at the department of Hajj, Waqf and Zakah, Malaysia - Ali, H.M.; Basir, S.A.; Ahmadun, M. (Universiti Sultan Azlan Shah, 2016)
The MS 1900 is an Islamic Quality Management System (QMS) which was launched by the Government of Malaysia in 2005. It is a structured system to assist organisations to deliver products and services that meet customer requirements, as well as the regulatory requirements and dictates of the Shari'ah (Islamic commandments). The Shari'ah requirements are additional to the requirements of ISO 9001, and aim to close the gap between the ISO 9001 standard and the Islamic perspective. MS 1900 has attracted considerable attention from Malaysian organizations but only a number of empirical studies have analysed the process of its implementation. Additionally, organisations that have successfully obtained QMS certification are still plagued with problems. Therefore, there is a need to study how MS 1900 is being implemented in certified organisations. The objective of this study is to examine activities conducted within the MS 1900 implementation process at the Department of Hajj (Muslim pilgrimage), Waqf and Zakah (DHWZ) in Malaysia and explore the benefits accrued from its implementation. A qualitative approach and case study strategy was used to investigate MS 1900 implementation at the DHWZ. Semistructured interviews were employed as the main data collection method to obtain in-depth information on the subject. Interviews were then triangulated with information from documents. The study found six main activities that were undertaken in MS 1900 implementation at the DHWZ, namely gap analysis, preparing the documentation, creating quality groups, implementing work procedures, as well as internal and external audits. The study also identified three benefits accrued from MS 1900 implementation; that is achieving the client's charter, the listing of being an outstanding religious department and systematic job management. The MS 1900 implementation has also helped managers implement strategic planning at the DHWZ. This study adds to knowledge of the emergence and development of the Islamic QMS MS 1900 and contributes particular insights into its implementation within Malaysian Islamic institutions. Findings from this paper could be used by managers in government or private institutions as a guideline in their endeavours to implement the MS 1900 effectively.